Theta phase coherence in visual mismatch responses involved in access processing to visual awareness - Kurita, Yuki; Urakawa, Tomokazu; Araki, Osamu (Frontiers in Human Neuroscience, 2023)
The electroencephalographic brain response to a deviation from the preceding sequential regularity of visual events, called visual mismatch negativity (vMMN), is well known to reflect automatic visual change detection. Our preliminary study showed a significant correlation between the enhancement of the vMMN amplitude and facilitation of perceptual alternation in binocular rivalry when the deviant stimulus was presented unconsciously. This implies that the vMMN is relevant to access processing, in which the unconscious stimulus is consciously perceived. Recent studies have reported that theta band oscillation evoked by a deviant stimulus is involved in evoking vMMN. However, it has not been clarified whether theta band oscillation associated with vMMN is also relevant to access processing. In the present study, we analyze the correlations between event-related spectral perturbation (ERSP) and inter-trial phase coherence (ITPC) in the theta band and the proportion of perceptual alternation from before to after the presentation of deviation in the same experimental paradigm as in our previous study. We found that an increase in ITPC in the theta band was significantly correlated with facilitation of perceptual alternation when the deviant was presented unconsciously, but there was no significant correlation in ERSP. The results indicate that theta phase coherence underlying the vMMN is relevant to the neural processing that the unconscious stimulus is consciously perceived.